2019
DOI: 10.1186/s13099-019-0305-x
|View full text |Cite
|
Sign up to set email alerts
|

High primary resistance to metronidazole and levofloxacin, and a moderate resistance to clarithromycin in Helicobacter pylori isolated from Karnataka patients

Abstract: Background Due to increased prevalence of H. pylori antimicrobial resistance worldwide and more importantly the resistance patterns vary between different geographical regions, it is important to survey local H. pylori antibiotic resistance profile to provide physicians with more informed drug choices to better treat H. pylori infection. To our knowledge, this is the first study to examine the prevalence of antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…28 Moreover, the strategy employed by H pylori for clarithromycin resistance has been elucidated mainly due to mutations at nucleotide positions (A2142G, A2143G, A2142C, A2146, A2147G, and G2224A) in the 23S rRNA. [29][30][31] Despite high prevalence of H pylori in Bangladesh, little is known about the local lineages or the local prevalence of particular genotypes for cagA or vacA and babA genotypes and any associations with disease severity. 32 Therefore, this study was directed to evalu-…”
Section: Introductionmentioning
confidence: 99%
“…28 Moreover, the strategy employed by H pylori for clarithromycin resistance has been elucidated mainly due to mutations at nucleotide positions (A2142G, A2143G, A2142C, A2146, A2147G, and G2224A) in the 23S rRNA. [29][30][31] Despite high prevalence of H pylori in Bangladesh, little is known about the local lineages or the local prevalence of particular genotypes for cagA or vacA and babA genotypes and any associations with disease severity. 32 Therefore, this study was directed to evalu-…”
Section: Introductionmentioning
confidence: 99%
“…An unprecedented number of studies last year reported on the important topic of antimicrobial resistance of H pylori strains 24‐60 . These are outlined in Table 1.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…The resistance breakpoints of CLA and LEV were defined as >0.5 μg/mL and >1 μg/mL, as previously suggested. 27…”
Section: Mic Determinationmentioning
confidence: 99%